2017
DOI: 10.12913/22998624/73820
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Thermal Cycling on the Tensile Behavior of CF/AL Fiber Metal Laminates

Abstract: The objective of this research work was to estimate the effect of thermal cycling on the tensile behavior of CARALL composites. Fiber metal laminates (FMLs), based on 2D woven carbon fabric and 2024-T3 Alclad aluminum alloy sheet were manufactured by pressure molding technique followed by hand layup method. Before fabrication, aluminum sheets were anodized with phosphoric acid to produce a micro porous alumina layer on surface. This microporous layer is beneficial to produce a strong bond between the metal and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…The effect of stacking sequence and fibers orientation is investigated on mechanical behaviors of the FMLs such as impact (Asaee and Taheri, 2016;Yaghoubi and Liaw, 2013;, tensile (Chandrasekar et al, 2019;Zareei et al, 2019), and flexural behavior (Azghan and Eslami-Farsani, 2018;Chandrasekar et al, 2019;Sharma et al, 2017). Also, several studies have reported the thermal cycling effects on mechanical properties of the FMLs (da Costa et al, 2012;Khalili et al, 2017;Noor et al, 2017). However, there are limited cases, studying the thermal cycling influence on different stacking sequences of the FMLs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of stacking sequence and fibers orientation is investigated on mechanical behaviors of the FMLs such as impact (Asaee and Taheri, 2016;Yaghoubi and Liaw, 2013;, tensile (Chandrasekar et al, 2019;Zareei et al, 2019), and flexural behavior (Azghan and Eslami-Farsani, 2018;Chandrasekar et al, 2019;Sharma et al, 2017). Also, several studies have reported the thermal cycling effects on mechanical properties of the FMLs (da Costa et al, 2012;Khalili et al, 2017;Noor et al, 2017). However, there are limited cases, studying the thermal cycling influence on different stacking sequences of the FMLs.…”
Section: Introductionmentioning
confidence: 99%
“…They observed that the thermal shock cycles did not result in significant micro-structural changes in the FML. Farhan Noor et al (2017) carried out experimental research regarding the effect of thermal cycling on the tensile properties of aluminum-epoxy/carbon fibers. They observed that the tensile strength was increased after 10 thermal cycles.…”
Section: Introductionmentioning
confidence: 99%
“…The basalt plastic armature of periodic profile (BPA) is used in construction of industrial structures, electric power facilities, in road construction, in light arched building structures, to which demands for climatic and corrosion resistance are made. Advantages of polymeric materials reinforced with basalt fibers are discussed in a number of works [1, 2, 3, 4, 5, 6, 7, 8, 9, 10] according to mechanical parameters, cost, resistance to aggressive environments, and biological resistance.…”
Section: Introductionmentioning
confidence: 99%
“…A similar comparison was made in [5, 6, 7] and it is shown that the ultimate tensile strength, ultimate bending strength, ultimate shear strength, and moduli of elasticity in tension, bending and shear are not inferior in their durability to the glass-reinforced plastics. In [8, 9, 10], resistance of basalt plastics to the action of low, high temperatures and thermal cycles was studied and stability of these materials to the indicated effects was shown. In [11, 12], analogous conclusions about the high stability of BPA against the action of aggressive media were obtained after evaluating the effect of water, salt and alkaline solutions at normal and increased temperatures on the mechanical properties of rods with diameters of 11–12 mm.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation